(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
This study showed the basic features of corporate tax in Iraq by showing what was in the Income Tax Law in force .The study aims of this to indicate the role of tax corprates in tax revenue and then the possibility of strengthening the revenue of this tax as an important source of local funding sources in the form that is with him reduce dependence on oil revenues to finance the general budget in Iraq, the risks and the study found a number of conclusions from the most important: that the corporate tax comes in the introduction to the components of the income tax structure in terms of relative importance and formed a revenue source of prime The gross proceeds of the income tax in Iraq, where it contributed to more than a quarter of that outcome average for the period 2005-2010 and more than a third of the contribution of the study proceeds as an average for the last three years of the study period, a mounting indication to the importance of this tax in this area. The study concluded of the number of recommendations that could contribute to strengthen this tax in tax revenue in Iraq.